Hadith #3626 - Sunan Abi Dawud - Abd al-Whab bin Njd'h عبد الوهاب بن نجدة; Auf bin Malik bin Nadlah عوف بن مالك بن نضلة - أبو الأحوص; Baqiyya bin al-Walid bin Sa'aid بقية بن الوليد بن صائد; Khalid bin Ma'dan خالد بن معدان; Musa bin Mrwan موسى بن مروان; Syf bin Sulaiman سيف بن سليمان (Sunan Abi Dawud)
The Holy Prophet (ﷺ) said to Ibn Suriya’: I remind you by Allah Who saved you from the people of Pharaoh, made you cover the sea, gave you the shade of clouds, sent down to you manna and quails, sent down you Torah to Moses, do you find stoning (for adultery) in your Book? He said: You have reminded me by the Great. It is not possible for me to belie you. He then transmitted the rest of the tradition.
Grade: Sahih